Challenges and Opportunities in the Implementation of the Local Government Act 2019 in Khyber Pakhtunkhwa - Anwar Sadat (`, 2025)
The Local Government Act (LGA) 2019 of Khyber Pakhtunkhwa (KP) represents a transformative effort toward devolved governance in Pakistan. This article critically examines the implementation of the Act, exploring the institutional, political, and financial dynamics shaping its execution. The LGA 2019 was introduced with the aim of strengthening grassroots democracy, ensuring citizen participation, and improving service delivery by devolving administrative powers to the tehsil level. However, the implementation of the Act has encountered several challenges, including political resistance, bureaucratic inertia, ambiguity in rules of business, and delayed local elections. Capacity constraints within local institutions and the non-release of development funds have further hindered the functional autonomy of local councils. This study also investigates the emerging opportunities within the current local governance framework. These include the potential for enhanced citizen engagement, empowerment of women and marginalized communities, the institutionalization of tehsil-level administration, and the role of digital technologies in promoting transparency and accountability. Through a synthesis of stakeholder perspectives including local representatives, government officials, civil society actors, and academics the article identifies the core strengths of the Act and areas requiring policy attention. The paper concludes with concrete policy recommendations, such as institutional training, timely elections, fiscal decentralization, civic education campaigns, and legislative reforms. By addressing these gaps, the KP government can realize the full potential of the LGA 2019 and build a more inclusive, accountable, and effective system of local governance in Pakistan. Keywords: Local Government Act 2019, Khyber Pakhtunkhwa, Decentralization, Governance, Tehsil Administration, Civic Participation, Fiscal Devolution, Institutional Capacity